The study of drug utilization of upper respiratory tract infection (URTI), at outpatient department of Hospital Tengku Ampuan Rahimah, Klang, Selangor: a prescription analysis study - Mohamad Rodzi, Nur Hida (2015)
Background: Drug utilization study of upper respiratory tract infection, (URTI), was important to be reviewed because the drugs are commonly used in hospital setting. Thus, this study aims to evaluate the drug utilization in every category of age and gender based on class of drug and adherence of prescriber to clinical practice guideline in management of URTI. Methodology: This is retrospective prescription study. 9114 prescription was collected from outpatient department of HT AR and was used in gathering data. Result: From review of 410 prescription with URTI, the most commonly prescribed drug were antihistamine 96.7% followed by paracetamol 55.2%, antibiotic 30.6%, vitamin C 19.6%, gargle preparation 13,9% and cough preparation 12.1 %. Out of30.6%, antibiotic combination of Amoxicilin and Clavulanate was commonly prescribed by doctors by which 46 (16. 7%) while diphenhydramine was the first choice for antihistamine by 115 (40.9%) prescriptions. Conclusion: The result of drug use in URTI especially with antibiotic was majority in line with the rational use of the drug but most of the patient receive non-antibiotic drug due to a few reasons.